1999
DOI: 10.1017/s0790966700005528
|View full text |Cite
|
Sign up to set email alerts
|

Outcome studies in schizophrenia

Abstract: Objectives:To outline the limitations of traditional studies of outcome in schizophrenia and to review the findings arising from ‘first episode’ psychosis studies.Method:An extensive literature search was performed and relevant papers were examined and analysed.Results:Current knowledge regarding outcome predictors in schizophrenia has primarily been derived from a series of ‘consecutive admission’ and ‘long-term follow-back’ studies. However, methodological considerations may limit the generalisability of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Third, firstepisode studies are not biased toward patients who experience multiple hospital admissions. 9 The main aim of this review, therefore, is to apply systematic techniques of data ascertainment, quality assessment, data extraction, and synthesis to first-episode cohort studies to establish whether they showed evidence of an association between DUP and outcome.…”
Section: Uration Of Untreatedmentioning
confidence: 99%
“…Third, firstepisode studies are not biased toward patients who experience multiple hospital admissions. 9 The main aim of this review, therefore, is to apply systematic techniques of data ascertainment, quality assessment, data extraction, and synthesis to first-episode cohort studies to establish whether they showed evidence of an association between DUP and outcome.…”
Section: Uration Of Untreatedmentioning
confidence: 99%
“…Longitudinal studies have provided most of our knowledge to date on the course and outcome of schizophrenia. However, most of these studies relied on non-first-episode cohorts and were biased towards patients who experienced multiple hospital admissions and included patients at varying stages of illness with an over-representation of chronic cases (Browne et al 1999). In recent times a number of studies have re-examined the area of outcome in more representative samples by including only cases of first-episode psychosis (Singh et al .…”
Section: Introductionmentioning
confidence: 99%
“…The last two decades has witnessed the emergence of follow‐up studies focusing upon first‐episode psychosis (FEP) 2–4 and first‐episode schizophrenia cohorts, 5–9 in the wake of earlier landmark long‐term follow‐up studies examining functional and clinical outcomes in schizophrenia cohorts 10–15 . Such prospective first‐episode studies provide the opportunity to assess prognosis among a cohort, at the same phase of illness, free from the confounding effects of previous treatment interventions or secondary disability 16,17 …”
Section: Introductionmentioning
confidence: 99%